Teachers' workload in a project-led engineering education approach - Alves, Anabela Carvalho (2009)
This paper presents a detailed list of activities, carried out by a team of teachers, while organizing and running an Interdisciplinary Project-Led Education (PLE) methodology for a full semester. The study was undertaken at the Engineering School of University of Minho, Portugal. It was based on a first year, first semester of the Integrated Master Degree in Industrial Management and Engineering (IME). The full PLE activities-related workload was accounted on a man-hour basis. Nineteen coordination activities were identified and the respective durations and frequencies were accounted. One semester of IME PLE requires a total of 569 man-hours. The project involved a much greater number of teachers and other staff when compared to a traditional semester. The most time-consuming activities were spotted and strategies and measures to deal with the resulting workload were discussed and some of them are proposed for implementation in future editions of the PLE methodology. Those proposals were considered more efficient ways to rationalize the use of teachers’ time.